Usability Evaluation of The Paket Agung Village Website Using System Usability Scale (SUS) Method - Ketut Utut Arta Gunawan; I Made Edy Listartha; I Nyoman Tri Anindia Putra (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
The Paket Agung Village website is an important public information resource for the community, however, since its launch, the effectiveness and efficiency of its use from the user perspective have never been measured. This research aims to evaluate the website’s usability and provide recommendations for improvement. The evaluation was conducted using the System Usability Scale (SUS) method, involving 20 respondents who are residents of Paket Agung, supplemented by 3 open-ended questions at the end of the survey. The results show that the average SUS score obtained was 61.5. Based on interpretation standards, the Paket Agung Village website is categorized as having a Marginal level of acceptability with a Grade D rating. These results indicate that the website is accessible and usable, but does not yet provide an optimal user experience. The main issues identified are a lack of comprehensive information, numerous empty or unfilled menus, and a lack of regular content updates. As a recommendation, the website administrators are advised to fill in and update the content in the available menus to increase public trust and interest in visiting the site. For future researchers, it is recommended to combine the SUS method with other methods or use a more comprehensive method to obtain a more in-depth analysis,